The nuclear safety and nuclear security interface : approaches and national experiences (Technical reports series (International Atomic Energy Agency), 2021)
"Nuclear safety and nuclear security share the same goal: to protect individuals, the public and the environment from harmful effects of ionizing radiation. However, the activities that address nuclear safety and nuclear security are different, and actions taken to strengthen nuclear safety may affect nuclear safety and nuclear security positively or negatively, and vice versa. It is therefore essential to establish a well coordinated approach to managing the interface between nuclear safety and nuclear security so that relevant measures are implemented in a manner that aims to capitalize on opportunities that may be available for mutual enhancement without compromising either nuclear safety or nuclear security. The responsibility for nuclear safety and nuclear security within a State rests entirely with that State. In this context, the importance of international cooperation and the central role of the IAEA is widely recognized. The IAEA assists Member States in establishing or strengthening their nuclear safety infrastructure as well as their nuclear security infrastructure. In addition, it provides support to establish synergy between both infrastructures to ensure that actions taken in the two fields compliment rather than compromise each other. The interface between nuclear safety and nuclear security is highlighted in IAEA safety standards and nuclear security guidance. This publication was developed from the exchange of information, experiences and practices by participating Member States at the IAEA Technical Meeting on Safety and Security Interface -- Approaches and National Experiences, held in Vienna in 2018. The information presented in this publication summarizes the views expressed by the participants during the technical meeting; it is not a consensus report"--The Foreword